A Review on Child Education and Development Theories - Samapti Paul, (AG Volumes, 2022)
Early childhood education is a critical component of a person's whole life experience and development. When a kid turns two, they begin their formal schooling. A child's education can only begin with a solid foundation laid by parents and educators. The early years of a child's life are critical, and both their parents and instructors at school must give them their full attention. It is only when they are able to convey efficient information to them in regards to academic ideas, play activities, art and craft projects, health and physical fitness, sports and games, the environment and social graces that they will be able to participate effectively in the educational process and achieve success.